EasyQuick Pulasan tablet cordial / Nurul Amirah Mohamed Shariff ... [et al.] - Mohamed Shariff, Nurul Amirah; Edsamara, Nurul Najihah; Mohd Samsudin, Siti Aisyah; Mat Daud, Ummi Suhana; Mohamed, Suraya Hani (2023)
The beverage industry or also known as the drink industry has become one of the largest industries due to the rising of customer demand all over the world (Uzuner & Cekmecelioglu, 2019). Besides, beverages have seen a rise in market share minute by minute as one of the most important industries that fulfill daily human needs. The beverage industry produces two main products which are drinks and ready-to-drink products. Moreover, the globe has recently been introduced to a wide range of new inventions and innovations in the beverage industry. The examples of beverage industry products are bottled water, milk products, soft drinks and cordial. Cordial is a concentrated syrup that usually comes in liquid form that is used in beverage making and there is a variety of cordial flavours that have been introduced to the market. By observing the existing cordial nowadays, there are several improvements and innovations that can be made to make the daily life of customers as well as the consumers easier. As is known, people nowadays demand for the things that can give convenience, require less energy and short time as they lack of time. Therefore, EasyQuick Enterprise introduce a new product that has been innovated from the existing of liquid cordial which is EasyQuick Pulasan tablet cordial. This cordial's innovation is that it is available in tablet form rather than liquid form, which is much more practical for both customers and consumers. Although making a drink from a liquid cordial does not really take much time, and people can just buy ready-to-drinks products, this innovation was introduced to help people save time and energy, as well as to potentially boost their health.